Diversidade e reconhecimento da diferença: um estudo no âmbito organizacional - Cacilda Nacur Lorentz (2014)
This thesis discusses issues related to diversity in the organizational context. Its central objective is to identify relations established between the conceptions of diversity shared by senior management, by managers and professionals responsible for diversity policies and by other employees of the organizations surveyed and analyze the consequences of these inter-relations in terms of recognition for those who work in them. The study of diversity is complex, broad and paradoxical and it is fragmented and dispersed under the protection of different classifications, such as race, ethnicity, gender, religious beliefs, sexual orientation, disability, and nationalities (NKOMO; COX JR., 1998; BENTO, 2000; GALEÃO-SILVA; ALVES, 2002; HANASHIRO; CARVALHO, 2005; PEREIRA; HANASHIRO, 2007, 2010; HANASHIRO, 2008; CARVALHO-FREITAS, 2009; CONCEIÇÃO et al., 2011; FREITAS, 2012; DINIZ et al., 2013). In this research, diversity is treated in the scope of studies on organizational behavior, in an analysis of the individual. Although in organizational discussion forums a functionalist view on diversity and its management predominates, here are incorporated discussions more critical and based on a post-structuralist perspective. For such, one relies on the Derridean deconstruction approach, which allows to break with the traditional binary reductionist view on various groups. Also, discussions on the theory of recognition by Axel Honneth (2003) are incorporated. In terms of methodology, it is a quantitative and qualitative research using in-depth interviews, focus groups and questionnaires submitted to discourse analysis and multivariated data analysis, respectively. The sample consisted of four organizations of the mining and steelmaking industry. In the qualitative approach 9 focus groups and 15 interviews were conducted; in the quantitative, the sample consisted of 759 questionnaires. Among the conclusions, it is highlighted: a) the identification of seven significant dimensions of diversity - gender, race/color, sexual orientation, people with disability, culture, generation and religion - each of them with their specificities; b) the dimension race/color proved to be the most significant in the construction of the concept of diversity - that is, for the people who participated in this research diversity refers primarily to racial differences; c) the different conceptions of diversity were shown more in function of values and individual experiences the interviewees had than of the positions (hierarchical levels) they occupied; d) difference and diversity were associated, being the first one explicative of the second; e) even though most of the time moving away from the praxis, the existence of organizational policies for diversity favors the perception of appropriate practices for coexistence of diverse groups in the workplace; and f) in the organizational environment there is a close relationship between the conceptions of diversity and diversity management, which effects relate to the perceptions of recognition. Among the limitations of this research, it is highlighted: a) delimiting to the segments studied, which have specificities and characteristics; b) not being able to deepen the understanding of the perception of employees whose responses were coming from the questionnaires; and c) not being able to verify recognition perception of people belonging to minority groups. As a suggestion for conduction of further research, it is proposed reapplying the questionnaires here developed, to verify if there is recurrence of responses patterns.